Promoting active travel for all in European urban regions. A review of evaluated initiatives. (Research Paper). - Schabus, Elise (My University, 2020)
Non-communicable diseases or so-called ‘Lifestyle diseases’ such as coronary heart diseases or diabetes are a major threat to public health in industrialised countries. Physical inactivity is believed to be one essential factor for the increase of lifestyle diseases in Europe. ‘Walking and Cycling’ and its embedment in everyday life (active travel) could become part of the solution to the decrease of lifestyle diseases in European cities. The aim of this review is to provide an overview of recent effectiveness studies on active travel interventions in European cities. It raises the question which barriers and facilitators are addressed, what groups are reached by different initiatives if and how most people can be reached. Methods:A systematic search for evaluation studies of active travel initiatives in European cities was conducted in four electronic Databases (PubMed, EBSCO, TRID and Web of Science). Included studies were published between June 2011 and May 2016 in English or German.
Keywords: Gesundheitsförderung; Fahrradbenutzung; Literaturstudie; Gehen